1981
DOI: 10.1017/s0033291700041258
|View full text |Cite
|
Sign up to set email alerts
|

The perception of drinking roles by recovering problem drinkers

Abstract: SynopsisThe perception of and attitude to drinking patterns in recovering problem drinkers (N= 29) is analysed, utilizing a similar methodology to that of Richard & Burley (1978). Fault is found, however, in the latter study both in a failure to define variables and in the authors' statistical handling of the results. In the present study, it was found that controlled drinking is only seen as close to the problem drinker's concept of himself when it entails reasonably high levels of consumption. The import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The remaining three studies lend some insight as to the content of the drinking-related self-schema among heavy drinkers. McCartney and O’Donnell (1981) was the first of the studies to associate traits and attributes with drinking-related self-conceptualizations. Researchers had 29 men and women, admitted to inpatient treatment for an AUD, rate how they perceived their own personality traits and personal attributes on a set of bipolar adjective pairs, as well as how they perceived the disposition of drinking roles—including total abstainer, heavy controlled drinker, light controlled drinker, and alcoholic—by ascribing specific traits and attributes to a variety of drinking roles, and then used a formula to calculate psychological distance.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining three studies lend some insight as to the content of the drinking-related self-schema among heavy drinkers. McCartney and O’Donnell (1981) was the first of the studies to associate traits and attributes with drinking-related self-conceptualizations. Researchers had 29 men and women, admitted to inpatient treatment for an AUD, rate how they perceived their own personality traits and personal attributes on a set of bipolar adjective pairs, as well as how they perceived the disposition of drinking roles—including total abstainer, heavy controlled drinker, light controlled drinker, and alcoholic—by ascribing specific traits and attributes to a variety of drinking roles, and then used a formula to calculate psychological distance.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers had 29 men and women, admitted to inpatient treatment for an AUD, rate how they perceived their own personality traits and personal attributes on a set of bipolar adjective pairs, as well as how they perceived the disposition of drinking roles—including total abstainer, heavy controlled drinker, light controlled drinker, and alcoholic—by ascribing specific traits and attributes to a variety of drinking roles, and then used a formula to calculate psychological distance. Results indicated that the greatest psychological distance existed between the traits ascribed to oneself and those attributed to the conceptualization of alcoholic, and the closest distance was between one’s self and heavy controlled drinker (McCartney & O’Donnell, 1981). The authors concluded that men and women with a diagnosable AUD were most likely to see one’s self as a heavy controlled drinker, and were least likely to see one’s self as alcoholic.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations